PENINGKATAN PENGETAHUANSISWA/SISWI SMA NEGERI 5 KOTA LANGSAKECAMATANLANGSA BARODENGANPENYULUHANMANAJEMEN PENGELOLAAN SAMPAH YANG BAIK - Srie Wahyuni; Deasy Amanda Valentine (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
One thing that is still a problem in Indonesia is the pile of garbage. there is still a lot of plastic waste produced by schools every day. The limited knowledge and skills of resources using appropriate technology is an obstacle for the school. Therefore, it is important to increase students' knowledge of good waste management. The targets for this community service activity are students of SMA Negeri 5 Langsa City through counseling. Due to the ongoing Covid-19 condition, this counseling was carried out only in 1 class while still adhering to health protocols. Based on the results of the discussion activities after the counseling, it was found that there was an understanding of students on how to manage waste properly and correctly.It is hoped that students will take an active role in increasing knowledge about waste management, especially in the school environment through counseling so that later they can create better health degrees